Techno-economic analysis of jatropha curcas biodiesel production in Malaysia / S Dalilla Abd Rahim - S Dalilla, Abd Rahim (2013)
The reduction of the high demand for crude oil is solved by increasing the production of biodiesel as the alternative fuel and at the same time can lessen the emissions of greenhouse gases. Most of the developing countries could not utilize and produce biodiesel at full potential due to some factors such as technical constraints, feedstock price, production cost, fossil fuel and taxation policy, depending on countries. This project paper evaluates the matters above by commencing a techno-economic and sensitivity analysis of biodiesel production in Malaysia by using feedstock from Jatropha curcas. The projected operating period is taken for 10 years starting from 2012 to 2022. The advantages of using non-edible Jatropha curcas as feedstock for biodiesel are it is drought-restraint plant, ability to grow anywhere, valuable properties of seeds, and known to have better cold properties compared to palm oil. The model of life cycle as well as the sensitivity analysis is taken as 50 ktons of biodiesel plant. Hence, the biodiesel production plant life cycle cost is estimated to be $315 million which yields a Jatropha biodiesel unit cost of $0.661/l over the project lifetime. The payback period was found to be 2.69 years, which is less than one third of the project lifetime. Jatropha biodiesel has proven to be feasible economically, recommended that in order to process and produce Jatropha biodiesel, the oil used should be in large quantities as the production cost to produce it is costly. The result of the analysis done in this paper would be able to provide future potential of Jatropha Curcas for biodiesel production in Malaysia.